Predictive value of ASCA and ANCA in inflammatory bowel diseases - D. A. Kuznetsova; S. V. Lapin; O. B. Shchukina; I. V. Gubonina; A. A. Kamanin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Serological diagnosis of inflammatory bowel diseases (IBD) is an additional tool not only for differential diagnosis, but also for individual prediction of the clinical course and long-term outcomes of Crohn’s disease (CD) and ulcerative colitis (UC).The objective was to assess the occurrence and capabilities of determining antibodies to Saccharomyces cerevisiae (ASCA) and antineutrophil cytoplasmic antibodies (ANCA) in predicting the clinical outcomes of IBD.Methods and materials. The study included 71 patients with CD, 26 with UC, and 21 with and 21 with IBD unclassified (IBDU). The comparison group consisted of 35 patients with other gastrointestinal diseases (irritable bowel syndrome with diarrhea (IBS-D), celiac disease, autoimmune gastritis (AIG)); the control group consisted of 24 apparently healthy individuals. The level of antibodies to ASCA IgA and IgG was measured by the ELISA method (ORGENTEC Diagnostika GmbH, Germany), ANCA IgG was determined by the IIF method of the Granulocyte Mosaic test system (EUROIMMUN AG, Germany).Results. The occurrence of ASCA IgA and IgG in patients with CD was 25 % and 38 %, which is significantly higher compared to patients with UC (0 % and 3.8 %), IBDU (5 % and 5 %), AIG (0 % and 5.3 %) respectively (p<0.05). Seropositivity for ANCA IgG in patients with UC was 54 %, which is significantly higher than in patients with CD, IBDU, AIG – 9.9 %, 9.5 % and 5.3 %, respectively (p<0.05). In patients with IBS-D and the control group, ASCA IgA and IgG and ANCA IgG were not detected. The combination of ASCA IgA and/or IgG seropositivity with a negative ANCA IgG result is more sensitive in differentiating CD from UC than the isolated determination of ASCA IgA (39.5 % vs. 25.3 %) with a specificity of 95.8 % and 96.5 %, respectively. The sensitivity of the combined detection of ANCA IgG with negative ASCA IgA and IgG results was comparable to the isolated detection of ANCA IgG – 52.5 % vs. 53.8 %, while the specificity increased to 94.6 %. ASCA IgA/G seropositivity serves as an unfavorable prognostic marker for the onset of CD before the age of 40, the stenotic and penetrating behavior, as well as the need for surgical treatment of the disease. Higher ANCA IgG titers were observed in patients with severe attack of UC (320 [320;640]) compared to mild attack (40 [40;80], p<0.05).Conclusion. ASCA and ANCA are highly specific markers of CD and UC, the combined determination of which makes it possible to increase the efficiency of serological examination not only in differential diagnosis, but also in personalized prediction of the clinical course of IBD.